2011
DOI: 10.1177/0883073810395937
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and Autistic Comorbidity in Fragile X Syndrome Across Ages

Abstract: Fragile X syndrome is caused by CGG trinucleotide repeat expansion within the fragile X mental retardation 1 gene, when repeat number exceeds 200. The typical psychiatric profile of fragile X syndrome patients includes cognitive and behavioral deficits, psychiatric comorbidity, and autistic characteristics. Specific psychiatric features have not yet been clarified, specifically in relationship to age and genetic characteristics. The objective of this study was to characterize psychiatric comorbidities in subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 48 publications
3
29
1
Order By: Relevance
“…Tics were reported in 16% of 152 people with FXS in a cohort from the United States, 52 and 36% and 45% of patients were reported to have motor and vocal tics, respectively, in a cohort of 22 patients with FXS from Israel. 53 The high frequency reported in the latter study may reflect confusion between stereotypies and tics in parent reports, which can be challenging to distinguish without history and neurologic examination data. The FXCRC database suggests that motor tics are uncommon in FXS, occurring in about 6% of affected people; this rate is not notably different from reports of combined motor and vocal tic frequency in the general population, 54 so no special management is indicated with respect to tics in FXS.…”
Section: Neurologic Disordersmentioning
confidence: 76%
“…Tics were reported in 16% of 152 people with FXS in a cohort from the United States, 52 and 36% and 45% of patients were reported to have motor and vocal tics, respectively, in a cohort of 22 patients with FXS from Israel. 53 The high frequency reported in the latter study may reflect confusion between stereotypies and tics in parent reports, which can be challenging to distinguish without history and neurologic examination data. The FXCRC database suggests that motor tics are uncommon in FXS, occurring in about 6% of affected people; this rate is not notably different from reports of combined motor and vocal tic frequency in the general population, 54 so no special management is indicated with respect to tics in FXS.…”
Section: Neurologic Disordersmentioning
confidence: 76%
“…Tranfaglia [40] reported that the presence of ADHD in those with FXS does not appear to follow a linear trajectory-young children may present as hypoactive, with hyperactivity increasing dramatically during the preschool years only to decline as children reach adolescence. Preliminary data suggest that the incidence of ADHD may be lower for adolescents than children and that different patterns of inattention and hyperactivity between those under and over 18 exist [43]. This developmental change might suggest which medications may be more effective and when.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, my observed frequency is in agreement with data from publications (5% to 60%). Cooccurrence of FXS and ASD is an additional risk factor in regard to central nervous system anomalies [6,9].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the psychiatric profile involves behavioral and cognitive symptoms, and includes hyperactivity, attention problems, anxiety, mood liability, aggression, self-injury, poor eye contact, self-talk, hand flapping, hand biting, as well as perseverative language [2,4,5]. Affected males with FXS are also at increased risk of experiencing liferelated psychiatric problems such as anxiety, depression and loneliness [6]. In my study, the presence of autism spectrum disorder was an important marker of independency.…”
Section: Discussionmentioning
confidence: 99%